Micromorfologia e anatomia floral das seções neotropicais de Bulbophyllum Thouars (Orchidaceae, Asparagales): considerações taxonômicas e evolutivas - Nunes, Elaine Lopes Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Bulbophyllum, the largest genus within Orchidaceae, is pantropical but its greatest diversity is found in the Asian Southeast. In the Neotropics, the genus comprises 60 species, being 49 of them found in Brazil. The greatest diversity of Neotropical species is in Brazilian Southeast, in transitional areas between the Atlantic Rainforest and Cerrado Vegetation. After the advent of molecular phylogenetic trees, and analysis of morphological data, six monophyletic Neotropical Bulbophyllum sections were recognised and recircumscribed: Bulbophyllaria, Furvescens, Napelli, Micranthae, Didactyle e Xiphizusa. However, information regarding floral anatomy and micromorphology for Neotropical species are available only for the labellum of six species. In addition, information on the pollination biology is available only to eight species. Considering the recent recircumscription of this group, and the paucity of information regarding floral features and their importance to pollination in Orchidaceae, this work aimed to analyse the floral anatomy and micromorphology of 30 Neotropical species, seven non-Neotropical species, and one Dendrobium species, in order to: characterise the flower of each section, help in species differentiation within section, and get a better understanding of the Neotropical group. The flowers of the Neotropical group can be characterised by free sepals, with sunken glandular trichomes on their abaxial surface; petals with a single collateral vascular bundle; labellum with a striate epidermis, with an adaxial sulcus that is usually secretory, and an abaxial keel with stomata; a papillose anther with four pollinia; a viscidium deriving from rostellar cells; and a 6-lobed ovary with one vascular bundle per lobe. Each section has common floral features and variable ones, which are discussed in each chapter with considerations regarding systematic and pollination implications. In general, the ornamentation of the outer periclinal...

Bulbophyllum, o maior gênero de Orchidaceae, possui distribuição pantropical mas sua maior diversidade concentra-se no sudeste Asiático. Na região Neotropical, o gênero é representado por 60 espécies, sendo que 49 delas ocorrem no Brasil. A maior diversidade de espécies neotropicais encontra-se no Sudeste brasileiro, nas regiões de contato entre o Cerrado e a Floresta Atlântica. Após o advento de filogenias moleculares, auxiliadas por dados morfológicos, foram reconhecidas e recircunscritas seis seções monofiléticas e neotropicais de Bulbophyllum: Bulbophyllaria, Furvescens, Napelli, Micranthae, Didactyle e Xiphizusa. Até o momento, informações sobre anatomia e micromorfologia florais para espécies neotropicais do gênero estão disponíveis apenas para seis espécies e tratam apenas do labelo. Além disso, informações sobre a polinização do grupo foram reportadas para apenas oito espécies. Considerando a recente recircunscrição do grupo, escassez de estudos sobre características florais e importância destas para a polinização em Orchidaceae, o objetivo deste trabalho foi analisar a micromorfologia e anatomia florais de 30 espécies neotropicais, bem como de sete espécies não-neotropicais e uma de Dendrobium, para: auxiliar na caracterização floral de cada seção, na diferenciação de espécies dentro das seções e para melhorar a compreensão do grupo como um todo. De forma geral, as flores das espécies das seções neotropicais de Bulbophyllum apresentam sépalas livres, com tricomas glandulares na face abaxial; pétalas com um feixe vascular colateral; labelo com epiderme estriada, com sulco na face adaxial, geralmente secretor, e uma quilha com estômatos na face abaxial; antera com epiderme papilosa e quatro polínias; presença de viscídio originado da desintegração das células do rostelo; ovário 6-lobado e com um feixe vascular por lobo. Cada seção apresenta características anatômicas e...
Keywords: Plant anatomy; Anatomia vegetal; Orquídea; Flores - Anatomia; Taxonomia vegetal; Flores - Morfologia